Sustainable Tourism Development in Vietnam in the Current Period - Anh, Le Hoang; Hien, Tran Thi; Sang, Nguyen Quang (Archives of Business Research, 2024)
Sustainable tourism development is currently an inevitable and effective direction for the tourism industry of Vietnam in particular and countries around the world in general. Vietnam has great potential for sustainable tourism development, from geographical location to natural and cultural resources. However, we also encounter many difficulties when developing sustainable tourism. This study points out the theoretical basis for sustainable tourism development; analyzes the current status of tourism development in Vietnam from 2015 to 2023; evaluates sustainable tourism development in Vietnam based on three aspects: Economy-Society-Environment; and examines the opportunities and challenges for sustainable tourism development in Vietnam. From that, several solutions will be proposed to develop sustainable tourism in Vietnam, making the tourism sector a key industry contributing to the ongoing development of Vietnam’s economy and society.